2017
DOI: 10.21475/ajcs.17.11.06.p382
|View full text |Cite
|
Sign up to set email alerts
|

Precision agriculture applied to soybean crop: Part II – Temporal stability of management zones

Abstract: Precision farming techniques have potential applications in the Brazilian Savannah owing to the spatial variability in crop yield. The objective of this study was to evaluate the temporal stability of management zones based on the measurement of apparent soil electrical conductivity (ECa). The study was performed in a field located in the Brazilian Savannah. During the 2011/2012 crop season, ECa was measured at 160 sampling points in a 47-ha area. ECa values were then grouped into classes using the fuzzy kmean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…OR "precision livestock production" OR "precision livestock farming" OR "precision irrigation" AND Tabela 6 -Ferramentas de agricultura de precisão na América do Sul (2008). (BOTTEGA et al, 2017;DE-MATTÊ et al, 2017;MACHADO;LANÇAS, 2016;GEBLER et al, 2015;KRAMER et al, 2014;NANNI et al, 2011).…”
Section: Definição De Adoção Tecnológicaunclassified
“…OR "precision livestock production" OR "precision livestock farming" OR "precision irrigation" AND Tabela 6 -Ferramentas de agricultura de precisão na América do Sul (2008). (BOTTEGA et al, 2017;DE-MATTÊ et al, 2017;MACHADO;LANÇAS, 2016;GEBLER et al, 2015;KRAMER et al, 2014;NANNI et al, 2011).…”
Section: Definição De Adoção Tecnológicaunclassified
“…Studies have shown a correlation between the apparent soil electrical conductivity (CEa) and chemical and physical attributes of the soil (MORAL et al, 2010;RODRÍGUEZ-PÉREZ et al, 2011;CORASSA et al, 2016) that influence the crop yield. The measurement of ECa is faster and cheaper than traditional soil sampling and laboratory analysis (BOTTEGA et al, 2017) which makes it a potential variable in MZ delimitation. In addition, ECa has been used as an indirect estimator of the variability existing in a production field (CORWIN;LESCH, 2003).…”
Section: Introductionmentioning
confidence: 99%